Behavioral biases and over-indebtedness in consumer credit: evidence from Malaysia - Fazelina Sahul Hamid (Cogent Economics & Finance)
Over-indebtedness in relation to consumer loans represents an important issue for consumers as it impacts their financial well-being. Identifying the risk factors associated with over-indebtedness is crucial in overcoming this problem. Existing literature shows that behavioral biases influence individuals’ financial decision making. This study analyses the relationship between behavioral biases and over-indebtedness among consumer loan holders in Malaysia. It aims to investigate whether self-control bias, overconfidence, mental accounting, and availability bias are linked to over-indebtedness. The analysis is done based on a sample of 433 credit card or personal loan holders. The results indicate that self-control bias is linked to higher overall over-indebtedness. Meanwhile, overconfidence and mental accounting are linked to lower overall over-indebtedness. Availability bias is shown to worsen credit card debt repayment decisions. These findings highlight the need for financial education programs that address self-control issues and raise awareness of behavioral biases, helping consumers make more informed financial decisions. Additionally, policymakers in Malaysia can leverage these insights to design targeted strategies that reduce over-indebtedness in managing consumer loans.